Effect of designed nursing instructions on knowledge and self-care behavior among patients with chemotherapy induced neutropenia - Sayed Abd-Almageed, Asmaa; ., . (International Journal of Advanced Nursing Studies, 2018)
Background:Chemotherapy-induced neutropenia (CIN) is the main dose limiting toxicity of systemic chemotherapy and it is associated with significant morbidity, mortality and treatment cost.Aim:Of the study was to evaluate effect of designed nursing instructions on knowledge and self-care behavior among patients with chemotherapy-induced neutropenia.Research design: Pre-post research design was utilized.Setting: The study was conducted at internal Medical Oncology Department at South Egypt Cancer Institute.Sample: Sixty adult patients with chemotherapy induced neutropenia. Tools of data collection: Tool (I): Patient assessment sheet, Tool (II): Self-care behavior assessment.Results: There was a highly statistically significant difference between pre and post applying of designed nursing instructions as regard patients' level of knowledge and self- care behavior of the studied patients (p<0.01).Conclusion: The designed nursing instructions improved knowledge and self-care behavior among patients with chemotherapy-induced neutropenia.Recommendation: Each neutropenic patient should be given a booklet including knowledge about neutropenia, importance, and how to practice standards self-care behavior. Education of patients and families are keys to prompt recognition about potentially life-threatening symptoms associated with neutropenia.Â Â